1994
DOI: 10.1002/etc.5620131010
|View full text |Cite
|
Sign up to set email alerts
|

Predation of ducks poisoned by white phosphorus: Exposure and risk to predators

Abstract: White phosphorus (P4) has been identified as the cause of mortality for dabbling ducks and swans at an estuanne salt marsh in Alaska Predation of ducks poisoned by P4 was monitored to assess the extent and range of predator exposures to P4 Avian tissues were analyzed for P4 by gas chromatography We observed that both sick and dead dabbling ducks were common prey of bald eagles (Hahaeetus leucocephalus), herring gulls (Larus argentatus), and common ravens (Corvus corax) Frank signs of P4 intoxication attracted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Other water birds that use the area but do not have apparent die‐offs include northern shovelers ( Anas clypeata ), American widgeon ( A. americana ), Canada geese ( Branta canadensis ), and snow geese ( Chen caerulescens ); these birds may be less exposed to P 4 because of food habits or habitat preferences. Avian predators or scavengers including bald eagles ( Haliaeetus leucocephalus ), golden eagles ( Aquila chrysaetos ), ravens ( Corvus corax ), and herring gulls ( Larus argentatus ) feed on dead or dying waterfowl and may be poisoned secondarily [4–6].…”
Section: Introductionmentioning
confidence: 99%
“…Other water birds that use the area but do not have apparent die‐offs include northern shovelers ( Anas clypeata ), American widgeon ( A. americana ), Canada geese ( Branta canadensis ), and snow geese ( Chen caerulescens ); these birds may be less exposed to P 4 because of food habits or habitat preferences. Avian predators or scavengers including bald eagles ( Haliaeetus leucocephalus ), golden eagles ( Aquila chrysaetos ), ravens ( Corvus corax ), and herring gulls ( Larus argentatus ) feed on dead or dying waterfowl and may be poisoned secondarily [4–6].…”
Section: Introductionmentioning
confidence: 99%
“…Of carcasses identified in 1992 to 1994, there were more than 100 of each of the susceptible species (green‐winged teal, mallard, and northern pintail), only 8 northern shovelers, and no American wigeon (Table 1). All 26 dead ducks collected in 1990 and 1991 [17–19] contained white phosphorus in their tissues so we assume that all ducks died of white phosphorus poisoning. Although wigeons and shovelers are less common at ERF, this cannot explain the differences in numbers of carcasses found (χ 2 = 195.28, d.f .…”
Section: Resultsmentioning
confidence: 99%
“…Addressing the yearly death rate of more than 1,000 dabbling ducks and swans over an extended period, these researchers showed that mortality was due to their ingestion of unspent P 4 particles located in the bottom sediments of the estuarine salt marsh. Furthermore, since sick or dead birds were susceptible to predation and scavenging, secondary transmission of P 4 occurred in species such as Bald Eagles and Gulls [22]. Racine et al [12] observed the behavior of birds that were affected in the wild and showed that it could be repeated in six adult Mallards gavaged once with 12 mg P 4 /kg in tricaprylin.…”
Section: Avian Oral Toxicity: Acutementioning
confidence: 99%